The effect of the presence and absence of the inflection marks on the category indication - البب, إبراهيم; نمر, مصطفى; منون, ياسر وليد (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Research into evidence is the most effective work done by the researcher, particularly the importance of a presumption in another, because it has a significant impact on enriching linguistic research in general, and grammar in particular, and has a significant impact on reaching highly important results. This research sought to demonstrate the impact of the presence and absence of expression marks at the rank, thus addressing the clarification of the relationship between the expressive mark and the expression of the researchers, monitored the stages of the development of the expressive mark from the actual existence to the scientific term that has stabilized in grammatical research, explained the meaning of rank as a language and terminology, and between its types, and spoke of the impact of expression marks on the freedom of rank, their impact together on the semantic meaning as well as their cooperation in generating musical melody through the rhyme, the letter of the Roy, the poetic weight, the Qur'anic comma. Also, it pointed out the impact of the absence of these marks on the preservation of rank, and referred to the means by which the rank uses to be able to possess freedom in the absence of expressive signs, all by pursuing the words of scholars in the old and modern lessons, together with applied models to clarify and deepen ideas.